Floristic patterns of epiphytes in the Brazilian Atlantic Forest, a biodiversity hotspot. (5th October 2015) - Leitman, Paula; Amorim, André M.; Sansevero, Jerônimo B. B.; Forzza, Rafaela C.
Abstract : To assess the main factors driving epiphytic angiosperm distribution throughout the Brazilian Atlantic Forest, we compiled 57 floristic surveys and analysed species composition under the influence of environmental variables, space and vegetation type using canonical correspondence analysis (CCA), similarity (Sorensen) and Mantel's tests. The indicator value index (IndVal) was used to find indicator species of each Brazilian Atlantic Forest vegetation type. Group sharpness analysis was performed in order to determine the appropriate group partition level. CCA showed a separation of the epiphytic flora reflecting temperature and rainfall gradients. Mantel's test showed that environment and space were highly correlated with floristic similarity. Cluster analysis, indicating floristic similarity, resolved five groups, mainly grouped by region. Clear differentiation of the Brazilian Atlantic Forest epiphytic flora on a north–south axis with a strong correlation with temperature and rainfall gradients was found. The role of space and environment on species composition varied according to distinct epiphytic species groups. In particular, for Bromeliaceae and Orchidaceae, the main factor associated with floristic similarity was space. Indicator species were found for all vegetation types apart from the Seasonal Semideciduous Forest that seemed to represent a subset of a more humid forest type. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 179, 587–601.